Novel loci for triglyceride/HDL-C ratio longitudinal change among subjects without T2D - Lihua Wang; Siyu Wang; Jason A. Anema; Vaha A. Moghaddam; Yanli Lu; Shiow Lin; E. Warwick Daw; Allison L. Kuipers; Iva Miljkovic; Michael Brent; Gary J. Patti; Bharat Thygarajan; et al. (Journal of Lipid Research)
Triglyceride (TG)/HDL-C ratio (THR) is a surrogate predictor of hyperinsulinemia. To identify novel genetic loci for THR change over time (ΔTHR), we conducted genome-wide association study (GWAS) and genome-wide linkage scan (GWLS) among nondiabetic Europeans from the Long Life Family Study (n = 1,384). Subjects with diabetes or on dyslipidemia medications were excluded. ΔTHR was derived using growth curve modeling and adjusted for age, sex, field centers, and principal components. GWAS used a linear mixed model accounting for familial relatedness. GWLS employed haplotype-based identity-by-descent estimation with 0.5 cM average spacing. Heritability of ΔTHR was moderate (46%). Our GWAS identified a significant locus at the LPL (P = 1.58e-9) for ΔTHR; this locus has been reported before influencing baseline THR levels. Our GWLS found significant linkage with a logarithm of the odds exceeding 3 on 3q28 (logarithm of the odds = 4.1). Using a subset of 25 linkage-enriched families, we assessed sequence elements under 3q28 and identified two novel variants (EIF4A2 [eukaryotic translation initiation factor 4A2]/ADIPOQ-rs114108468, p = 5e-6, minor allele frequency = 1.8%; TPRG1-rs16864075, p = 3e-6, minor allele frequency = 8%; accounted for ∼28% and ∼29% of the linkage, respectively). While the former variant was associated with EIF4A2 (p = 7e-5)/ADIPOQ (P = 3.49e-2) transcriptional levels, the latter variant was not associated with TPRG1 (P = 0.23) transcriptional levels. Replication in the Framingham Heart Study Offspring Cohort observed modest effect of these loci on ΔTHR. Our approach discovered two novel gene variants EIF4A2/ADIPOQ-rs114108468 and TPRG1-rs16864075 on 3q28 for ΔTHR among subjects without diabetes. Our findings provided novel insights into the molecular regulation of insulin resistance.